Problems and Challenges Empowering Human Resources (Hr) in Company Organization in Globalization Era - I Nyoman Putu Budiartha (Sociological Jurisprudence Journal, 2018)
Existence of Human resources (HR) as a worker is very important in the company because in addition as wrong one element in a company organization that helps business activities as well as an input element or input along with other elements in the process production either in the form of services or goods through the management process in the form output or output. Without any human resources or workers within the company, it is impossible that the company can move and run in producing goods and services in an effort to achieve company goals. There are several problems and challenges for HR workers in companies in the global era where the problems encountered can include: the competence of workers in global competition, population growth and unemployment widened the diversity of the world of work that requires creative innovation and organizational management issues and professionalism, labor protection, social and environmental responsibility. The company's future challenges can be internal challenges in the form of financial, sales, service, production and industrial relations of workers and as external challenges of technological advancement, global political economy and socio-cultural.